Police body worn cameras: a mixed method approach assessing perceptions of efficacy. Issue 3 (15th August 2016) - Pelfrey Jr, William V.; Keener, Steven
Abstract : Purpose: The importance of body-worn cameras (BWC) in policing cannot be overstated. This is not a hyperbolic statement – use of force incidents in Ferguson and Baltimore, the ensuing riots, coupled with critical long term implications for police community relations demonstrate the need for BWC data. Few studies have been published on the use of BWCs and little is known about officer perceptions, administrator decision making, and agency use of BWC data. No published studies incorporate qualitative data, which lends important context and depth, in the interpretation of officer survey data. The paper aims to discuss these issues. Design/methodology/approach: The current study presents a mixed-method study of a large university police agency prior to full implementation of BWC. A survey of patrol officers and supervisors, using a census approach with near full participation, coupled with focus group interviews, produced data on perceptions, concerns, and expectations of full BWC implementation. Findings: Findings point to officer concerns regarding the utilization of BWC data and administrative expectations regarding complaint reduction and officer assessment. Originality/value: Important implications regarding training and policy are presented. BWC data represent an important tool for agency decision makers but have numerous potential negative uses. Understanding officer concerns juxtaposed with administrator expectations, through both survey and qualitative data, advance the knowledge on BWC.